2014
DOI: 10.1007/s00586-014-3642-y
|View full text |Cite
|
Sign up to set email alerts
|

Anterior stand-alone fusion revisited: a prospective clinical, X-ray and CT investigation

Abstract: The current study delineates satisfactory clinical results following ASAF at the lumbosacral junction. Patient safety was demonstrated with acceptable complication and low reoperation rates. Radiological data demonstrated a significant reconstruction of lordosis at the lumbosacral junction. Solid interbody fusion was achieved in 97.3 % of all cases in a highly selected cohort with optimal predisposition for fusion. ASAF may serve to avoid a variety of negative side effects for a considerable number of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 81 publications
2
25
0
Order By: Relevance
“…In addition, the VAS and ODI scores decreased significantly after surgery compared to baseline. Studies by Siepe et al [3] and Allain et al [28] have shown similar results with significant improvement in disc height and foraminal height and decrease in VAS and ODI scores at each time point of follow-up after surgery. Subsidence of the implant into the vertebral endplate may lead to progressive lumbar deformity and recurrence of foraminal stenosis and neurological symptoms, which have been of concern to researchers.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…In addition, the VAS and ODI scores decreased significantly after surgery compared to baseline. Studies by Siepe et al [3] and Allain et al [28] have shown similar results with significant improvement in disc height and foraminal height and decrease in VAS and ODI scores at each time point of follow-up after surgery. Subsidence of the implant into the vertebral endplate may lead to progressive lumbar deformity and recurrence of foraminal stenosis and neurological symptoms, which have been of concern to researchers.…”
Section: Discussionmentioning
confidence: 57%
“…A biomechanical test revealed that the self-locking stand-alone cage could provide immediate stability that was equivalent to that with anterior plate or posterior pedicle screw fixation [27]. Clinical studies have also demonstrated that a high fusion rate (90.6% to 97.3%) with good clinical results could be achieved using these self-anchored designed stand-alone cages [3, 25, 28]. In our study all patients achieved solid fusion at the last follow-up which supported the hypothesis that these self-anchored stand-alone cages could provide immediate stability after surgery and reach high fusion rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intervertebral fusion rate: Assessed by the Siepe method for lumbar vertebral 3D CT reconstruction [23] .…”
Section: Radiograph Evaluation Indicesmentioning
confidence: 99%
“…Lack of substantial sclerotic changes in the recipient bone bed, visible bridging bone either through the cage or surrounding it as observed on anterior-posterior or lateral radiographs are criteria from some other studies. And also, it has been demonstrated that CT scan is essential to assess interbody fusions [4]. We have tried to employ X-ray to evaluate the PEEK-cages interbody fusion rate, but finally a thin-layer slicing CT scan had to be performed in the cases where bone fusion on plain radiographs was in doubt [5].…”
Section: Dear Editormentioning
confidence: 99%